2021
DOI: 10.2478/cpp-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the development of anxiety disorders - a literature review

Abstract: Introduction: The COVID-19 is a disease caused by the SARS-CoV-2 virus. A number of psychological symptoms have been identified in people living during the COVID-19 pandemic. Most of them are associated with widely understood anxiety disorders, which have always been a significant problem for mental health. Materials and methods: The available literature was reviewed on the Pubmed platform and from other sources. The analysis included original studies, reviews, meta-analyzes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, patients with a diagnosis of OCD had obsessions and compulsions that were related to the COVID-19 pandemic. It was also found that the pandemic did not have a significant impact on the symptoms of patients diagnosed with social phobia [6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, patients with a diagnosis of OCD had obsessions and compulsions that were related to the COVID-19 pandemic. It was also found that the pandemic did not have a significant impact on the symptoms of patients diagnosed with social phobia [6].…”
Section: Introductionmentioning
confidence: 96%
“…In Koch's 2021 review [6] of the impact of COVID-19 on anxiety disorders, an increased prevalence of anxiety-related symptoms was found in the general population during the COVID-19 pandemic. In addition, patients with a diagnosis of OCD had obsessions and compulsions that were related to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%